Approach to acute encephalitis in the intensive care unit. Issue 2 (13th April 2023) - Venkatesan, Arun; Habis, Ralph; Geocadin, Romergryko G.
Abstract : Purpose of review: Recent years have seen a dramatic increase in the identification of autoimmune encephalitis (AE) and the emergence of new causes of infectious encephalitis (IE). However, management of these patients remains challenging, with many requiring care in intensive care units. Here, we describe recent advances in the diagnosis and management of acute encephalitis. Recent findings: Advances in the identification of clinical presentations, neuroimaging biomarkers, and electroencephalogram patterns have enabled more rapid diagnosis of encephalitis. Newer modalities such as meningitis/encephalitis multiplex PCR panels, metagenomic next-generation sequencing, and phage display-based assays are being evaluated in an effort to improve detection of autoantibodies and pathogens. Specific advances in the treatment of AE include establishment of a systematic approach to first-line therapies and the development of newer second-line modalities. The role of immunomodulation and its applications in IE are actively being investigated. In the ICU, particular attention to status epilepticus, cerebral edema, and dysautonomia may improve outcomes. Summary: Substantial diagnostic delays still occur, with many cases left without an identified etiology. Antiviral therapies remain scarce, and optimal treatment regimens for AE still need to be clarified. Nevertheless, our understanding of diagnostic and therapeutic approaches to encephalitis is rapidly evolving.